2022
DOI: 10.1111/bjd.21018
|View full text |Cite
|
Sign up to set email alerts
|

Mogamulizumab induces long‐term immune restoration and reshapes tumour heterogeneity in Sézary syndrome*

Abstract: Summary Background Mogamulizumab, an anti‐CCR4 monoclonal antibody, has been shown to increase progression‐free survival in cutaneous T‐cell lymphoma. Objectives We hypothesized that besides the targeted depletion of Sézary cells (SCs), mogamulizumab may reshape the immune tumour microenvironment. Methods Both malignant and benign compartments from 26 patients with B2 stage Sézary syndrome before mogamulizumab initiation were prospectively analysed using KIR3DL2 and TCRVβ markers, serological markers and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 40 publications
0
13
0
1
Order By: Relevance
“…However, a real world SS cohort found that mogamulizumab, in addition to depleting benign CD4+ T cells, Tregs, and malignant T cells, also decreased CD8+ T cells and NK cells at one month of treatment. Longer-term follow-up in this cohort revealed the emergence of “immune restoration” involving expansion of naïve and stem memory CD4+ subsets with almost complete disappearance of pre-treatment exhausted lymphocytes (PD-1+ or TIGIT+ CD4+ T cells) and activated Tregs ( 205 ). In skin biopsies taken from patients with MAR, an increase in interferon-stimulated gene IFI44L and macrophages expressing CXCL11 and CXCL9 coupled with expansion of new T cell clones expressing CXCR3 (the cognate receptor for CXCL9/11) and genes important for cytotoxic effector function was observed, shedding new insight on the potential role tumor associated macrophages may play in generating prolonged remissions from mogamulizumab ( 206 ).…”
Section: Targeted Therapiesmentioning
confidence: 88%
See 1 more Smart Citation
“…However, a real world SS cohort found that mogamulizumab, in addition to depleting benign CD4+ T cells, Tregs, and malignant T cells, also decreased CD8+ T cells and NK cells at one month of treatment. Longer-term follow-up in this cohort revealed the emergence of “immune restoration” involving expansion of naïve and stem memory CD4+ subsets with almost complete disappearance of pre-treatment exhausted lymphocytes (PD-1+ or TIGIT+ CD4+ T cells) and activated Tregs ( 205 ). In skin biopsies taken from patients with MAR, an increase in interferon-stimulated gene IFI44L and macrophages expressing CXCL11 and CXCL9 coupled with expansion of new T cell clones expressing CXCR3 (the cognate receptor for CXCL9/11) and genes important for cytotoxic effector function was observed, shedding new insight on the potential role tumor associated macrophages may play in generating prolonged remissions from mogamulizumab ( 206 ).…”
Section: Targeted Therapiesmentioning
confidence: 88%
“…In skin biopsies taken from patients with MAR, an increase in interferon-stimulated gene IFI44L and macrophages expressing CXCL11 and CXCL9 coupled with expansion of new T cell clones expressing CXCR3 (the cognate receptor for CXCL9/11) and genes important for cytotoxic effector function was observed, shedding new insight on the potential role tumor associated macrophages may play in generating prolonged remissions from mogamulizumab ( 206 ). Despite favorable changes in the immune environment, disease relapse in the SS cohort appeared to be tied to the emergence of CCR4- malignant T cells ( 205 ).…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…Mogamulizumab, an anti-CCR4 monoclonal antibody has recently been approved by FDA and EMA following a phase III clinical trial which showed increased progression free survival (PFS) compared with the HDAC inhibitor, Vorinostat ( 21 ). Recently, it has emerged that Mogamulizumab also contributes to efficient immune restoration involving CD8+ as well as stem and memory CD4+ cells ( 90 ).…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“… 8 This has since come to be known as mogamulizumab-associated rash (MAR); some patients experiencing MAR, particularly those with SS, had improved clinical responses compared with those without MAR. 11 - 13 One explanation for this phenomenon is the immunomodulatory effect of mogamulizumab contributing to the restoration of efficient immunity through reduction of the number of CCR4+ malignant cells and benign T cells [including exhausted lymphocytes and activated regulatory T cells (Tregs)] and subsequent emergence of cluster of differentiation (CD)8+, naïve and stem cell memory CD4+ T cells. 11 - 13 …”
Section: Introductionmentioning
confidence: 99%
“… 11 - 13 One explanation for this phenomenon is the immunomodulatory effect of mogamulizumab contributing to the restoration of efficient immunity through reduction of the number of CCR4+ malignant cells and benign T cells [including exhausted lymphocytes and activated regulatory T cells (Tregs)] and subsequent emergence of cluster of differentiation (CD)8+, naïve and stem cell memory CD4+ T cells. 11 - 13 …”
Section: Introductionmentioning
confidence: 99%